First experimental validation of silicon-based sensors for monitoring ultra-high dose rate electron beams - Medina, Elisabetta; Ferro, Arianna; Abujami, Mohammad; Camperi, Aurora; Centis Vignali, Matteo; Data, Emanuele; Del Sarto, Damiano; Deut, Umberto; Di Martino, Fabio; Fadavi Mazinani, Mohammad; Ferrero, Marco; Ferrero, Veronica; et al. (Frontiers in Physics, 2024)
Monitoring ultra-high dose-rate (UHDR) beams is one of the multiple challenges posed by the emergent FLASH radiotherapy. Technologies (i.e., gas-filled ionization chambers) nowadays used in conventional radiotherapy are no longer effective when applied to UHDR regimes, due to the recombination effect they are affected by, and the time required to collect charges. Exploiting the expertise in the field of silicon sensors' applications into clinics, the medical physics group of the University and INFN Torino is investigating thin silicon sensors as possible candidates for UHDR beam monitoring, exploiting their excellent spatial resolution and well-developed technology. Silicon sensors of different thicknesses and active areas were tested at the SIT ElectronFlash machine (CPFR, Pisa) on 9 MeV electron beams and showed very good response linearity up to more than 10 Gy/pulse, confirming their potential for beam monitoring applications.